Association of empty nest with depressive symptom among Chinese elderly population: The China Longitudinal Aging Social Survey. Issue 26 (30th June 2022) - Zheng, Pianpian; Yang, Hanmo; Wang, Zhenjie
Abstract : Currently, empty nest has become one type of the family pattern among the old population and it influences the old population's mental health. The current study aimed to explore the association between the empty nest and depressive symptoms (DSs) among the elderly population in China. Data were obtained from baseline of the China Longitudinal Aging Social Survey. Logistic regression was used to examine the association between the empty nest and DS among Chinese older adults. In the current study, 48% of the subjects were empty-nest elderly. The prevalence of DS was 43.7% among the empty-nest old population, which was higher than the nonempty nesters. A positive association was found between the empty nest and DS; the odds ratio (95% confidence interval) was 1.28 (1.16–1.42). No matter living with a spouse or living alone, empty nesters were more likely to have DS than nonempty nesters. Empty nest is a risk factor for having DS among the old population in China, especially among those who live without a spouse. Our result is valuable for the development of special family support DS prevention programs for those who were empty nest.